1982
DOI: 10.1016/0033-5894(82)90057-6
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Reflection Study of Recessional Moraines beneath Lake Superior and Their Relationship to Regional Deglaciation

Abstract: Approximately 8000 km of continuous seismic reflection profiles throughout Lake Superior were examined for evidence of recessional moraines and other ice-margin deposits associated with the retreat of late Wisconsin ice. These features are correlated with the record of glacial-lake evolution in western Lake Superior. An offlapping sequence of glacial and glacial-lacustrine sediments overlying bedrock is recognized in west-central Lake Superior that is progressively younger to the northeast. The sequence underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 25 publications
2
23
0
Order By: Relevance
“…The generally transparent unit 1 corresponds to post-glacial sandy clays overlying varved glacial-lacustrine clay. The stratified unit 2 is probably glacial outwash material, and unit 3 is glacial till (Johnson, 1980;Landmesser et a/., 1982;Johnson er al., 1984). The subbottom reflections in the generally well-laminated unit 2 are often disrupted in the ring zone.…”
Section: Resultssupporting
confidence: 54%
See 3 more Smart Citations
“…The generally transparent unit 1 corresponds to post-glacial sandy clays overlying varved glacial-lacustrine clay. The stratified unit 2 is probably glacial outwash material, and unit 3 is glacial till (Johnson, 1980;Landmesser et a/., 1982;Johnson er al., 1984). The subbottom reflections in the generally well-laminated unit 2 are often disrupted in the ring zone.…”
Section: Resultssupporting
confidence: 54%
“…The lake bed is highly reflective in this area at distances of up to 30 km offshore. Seismic reflection studies suggest that these ridges may be glacial moraines (Landmesser et al, 1982), and thus the more reflective lake bed observed here may be due to coarser, glacially derived sediments at the surface. In the offshore reflective zone there are parallel lineated targets and occasional circular targets ('light' rings).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…topography of the bedrock surface and the total thickness of sediment above bedrock (Wold and Hutchinson, 1979;Wold et al, 1982). Landmesser et al (1982) used a subset of these data along with 3.5 kHz data that they collected in the central part of the lake to define three recessional moraines and related deposits, which are discussed further here. We collected seismic-reflection data using multiple systems in several areas of Lake Superior in order to better understand the glacial and post-glacial history of Lake Superior and Lake Agassiz.…”
mentioning
confidence: 99%